Profil Berpikir Kritis Siswa dalam Menyelesaikan Tugas Numerasi Kontekstual pada Pembelajaran Matematika - Eric Dwi Putra; Mochammad Fadil Djamali; Rini Nur Indah Sari; Diva Oliviya Mayantika; Selvita Risca Alifiana (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2026)
This study aims to describe students' critical thinking skills through contextual numeracy tasks in mathematics learning. This study uses a descriptive qualitative approach. The research subjects consisted of four students from class IX B, selected purposively based on their critical thinking skills, namely two students with high abilities and two students with low abilities. Data collection techniques included tests in the form of contextual numeracy tasks on congruence and similarity, observation, semi-structured interviews, and documentation. Data validity was obtained through source triangulation. Data analysis was based on critical thinking indicators, which included interpretation, analysis, evaluation, and inference. The results showed that students with high critical thinking skills were able to meet all critical thinking indicators, as demonstrated by their ability to understand the context of the problem, determine the appropriate solution strategy, evaluate the calculation results, and draw logical conclusions according to the context of the problem. Conversely, students with low critical thinking skills still experience difficulties in several indicators, particularly evaluation and inference, where students tend to lack rechecking and are unable to provide contextual explanations for the numerical answers obtained. These findings indicate that contextual numeracy tasks can be used to reveal variations in student’s critical thinking processes during mathematics learning. The implication of this research is that teachers need to design contextual numeracy tasks that explicitly require studentsto engage in interpretation, analysis, evaluation, and inference, thereby enabling their critical thinking skills to develop optimally